In Vitro Fermentation of Browsable Native Shrubs in New Zealand - Wangui JC; Millner JP; Kenyon PR; Tozer PR; Morel PCH; Pain SJ (MDPI (Basel, Switzerland), 2022)
Information on the nutritive value and in vitro fermentation characteristics of native shrubs in New Zealand is scant. This is despite their potential as alternatives to exotic trees and shrubs for supplementary fodder, and their mitigation of greenhouse gases and soil erosion on hill-country sheep and beef farms. The objectives of this study were to measure the in vitro fermentation gas production, predict the parameters of the in vitro fermentation kinetics and estimate the in vitro fermentation of volatile fatty acids (VFA), microbial biomass (MBM), and greenhouse gases of four native shrubs ( Coprosma robusta, Griselinia littoralis, Hoheria populnea, and Pittosporum crassifolium) and an exotic fodder tree species, Salix schwerinii. The total in vitro gas production was higher (p < 0.05) for the natives than for the S. schwerinii. A prediction using the single-pool model resulted in biologically incorrect negative in vitro total gas production from the immediately soluble fraction of the native shrubs. However, the dual pool model better predicted the in vitro total gas production and was in alignment with the measured in vitro fermentation end products. The in vitro VFA and greenhouse gas production from the fermentation of leaf and stem material was higher (p < 0.05), and the MBM lower (p < 0.05), for the native shrubs compared to the S. schwerinii. The lower in vitro total gas production, VFA, and greenhouse gases production and higher MBM of the S. schwerinii may be explained by the presence of condensed tannins (CT), although this was not measured and requires further study. In conclusion, the results from this study suggest that when consumed by ruminant livestock, browsable native shrubs can provide adequate energy and microbial protein, and that greenhouse-gas production from these species is within the ranges reported for typical New Zealand pastures.
Keywords: greenhouse gases; hill country; in vitro fermentation; native shrubs; volatile fatty acids